2022
DOI: 10.3389/fnins.2022.867021
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Circuits Supporting Development of Visual Naming Revealed by Intracranial Coherence Modulations

Abstract: BackgroundImprovement in visual naming abilities throughout the childhood and adolescence supports development of higher-order linguistic skills. We investigated neuronal circuits underlying improvement in the speed of visual naming with age, and age-related dynamics of these circuits.MethodsResponse times were electronically measured during an overt visual naming task in epilepsy patients undergoing stereo-EEG monitoring. Coherence modulations among pairs of neuroanatomic parcels were computed and analyzed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…39 Speech arrest was observed when stimulating bilateral inferior precentral gyri and left posterior SFG. 31 Sonoda's earlier study identified auditory sentence-listening sites distributed throughout more posterior STG and MTG, whereas HGM for sentence stimulus offsets and responses were found in posterior temporal and frontal regions. 40 This study also found HGM patterns for speech production when stimulating the Rolandic gyrus of either hemisphere.…”
Section: Stimulation Errors and Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…39 Speech arrest was observed when stimulating bilateral inferior precentral gyri and left posterior SFG. 31 Sonoda's earlier study identified auditory sentence-listening sites distributed throughout more posterior STG and MTG, whereas HGM for sentence stimulus offsets and responses were found in posterior temporal and frontal regions. 40 This study also found HGM patterns for speech production when stimulating the Rolandic gyrus of either hemisphere.…”
Section: Stimulation Errors and Resultsmentioning
confidence: 95%
“…A total of 353 children and young adults were evaluated, with possible patient overlap between the eight Cincinnati Children's cohort studies. [25][26][27][28][29][30][31][32] Location details, when available, are provided in as much detail as possible, and range in specificity from lobes to Brodmann areas based on reported information. Nearly all studies mapped frontal and temporal regions.…”
Section: Visual Naming Task With Esm (Sde or Seeg)mentioning
confidence: 99%
See 3 more Smart Citations